Human Factors Effects in Helicopter Maintenance: Proactive Monitoring and Controlling Techniques - Rashid, Hamadalneel Suliman Jumaa (Cranfield University, 2010)
Aviation maintenance errors account for between 13% and 23% of the global aviation incidents and accidents initiators, which require a wider global use of aviation maintenance safety improvement activities. The current research applies the Human Error Risk Management in Engineering Systems (HERMES) methodology that conceptualizes two main streams of study. These are the retrospective investigation of human errors within aviation maintenance contexts, and a prospective innovation of new tools that work to prevent errors occurring. In this research the impact of human reliability on aviation maintenance safety is investigated. Rotorcraft is taken as a focal case study. A new model to represent the accumulation of crucial maintenance human errors causal factors, within aviation maintenance companies, is introduced. A total of 804 recent maintenance-induced helicopter accidents were reviewed, from which 58 fatal accidents and serious incidents were thoroughly analysed using Human Factors Accident Classification System - Maintenance Extension (HFACS-ME). A 4th order of analysis is newly introduced into the HFACS-ME taxonomy under the notion of ‘Specific Failures’ for better analysis resolution and comprehensiveness. Hypothesizing that human factors errors within aviation maintenance industry can be more effectively managed by applying proactive monitoring and early error detecting techniques - at both organizational and individual levels, a proactive Aviation Maintenance Monitoring Process (AMMP) is formulated. AMMP is a holistic hybrid retrospective / prospective integrated process that is to be simultaneously and collectively implemented by main industry stake-holders - regulators, manufacturers and maintenance organisations. The aim is to proactively monitor the existence of human error causal factors that are initiated during design practices, manufacturing processes, or at later stages due to workplace conditions. As a result, such causal factors can be gradually eliminated to reduce the overall risk of maintenance errors. This generic AMMP model is based on a Root Cause Existence Scale (RCES) and a comprehensive sociotechnical user program, coded as ‘ErroDetect’, built applying the fuzzy Analytic Network Process (fuzzy ANP) theory. A total of 870 different assessment criteria were designed and then in-built within the software thus mapping the outcomes of the retrospective error causal factors investigative studies. Full simulation of the process is conducted, and then it was further validated practically in real world within industry for both design for maintainability within major rotorcraft manufacturer facilities, and for MRO’s performance safety enhancement. Validation results were thoroughly discussed. The AMMP is found to have significantly enhanced aircraft maintenance proactive safety for both designers and maintainers. The tool can also be adopted for regulation purposes.